Density currents affect the vertical evolution of dissolved organic matter chemistry in a large tributary of the Three Gorges Reservoir during the water-level rising period. (1st October 2021) - Wang, Kai; Li, Penghui; He, Chen; Shi, Quan; He, Ding
Highlights: Various DOM sources in surface, middle, and bottom were investigated in XXB. Property variations of DOM in water column were affected by reservoir construction-induced density current. Vertical variations of DOM could affect CO2 emission and carbon burial in reservoirs. Abstract: Reservoirs have boomed for clean energy in recent decades and interrupted the natural river ecosystem severely. Riverine dissolved organic matter (DOM), which regulates aquatic food web dynamics, water quality, and carbon storage, has been significantly impacted by reservoir construction. However, the vertical evolution of DOM properties and its controlling mechanisms in large reservoirs with hydrological management are not well investigated, limiting the understanding of carbon cycling ( e.g., CO2 emissions and carbon burial) in reservoirs. To fill this knowledge gap, multiple complementary techniques including optical spectroscopy and ultrahigh-resolution Fourier transform ion cyclotron resonance mass spectrometry were applied to track composition and property changes of DOM along the vertical profile in a large deep tributary of the world largest Three Gorges Reservoir (TGR) during the water-level rising period. The results indicated that middle and bottom water have relatively more terrestrial input and recalcitrant DOM, while surface water has relatively more autochthonous input and labile DOM. Integrated with the comprehensive analysis of DOM chemistry in a high-resolution vertical profile, the primary production and photodegradation in surface water, the density currents induced water intrusion from mainstream to tributaries, in middle water, and the biodegradation in bottom water are main factors controlling the vertical heterogeneity of reservoir DOM during the water-level rising period. This vertical increase of DOM recalcitrance likely contributes to the enhancement of organic carbon burial in TGR during the water-level rising period. All in all, this study provides new insight into the vertical variations of riverine DOM induced by reservoir construction, and emphasizes the important role of reservoir construction in carbon sequestration. Graphical abstract: Image, graphical abstract